Analisis Kelayakan Video Pembelajaran Fisika Pada Platform Youtube Materi Getaran dan Gelombang Kelas VIII SMP - Lolang, Enos; Andilolo, Jumiarti; Silka, Silka (Universitas PGRI Semarang, 2023)
This study aims to determine the feasibility of YouTube-based physics learning videos on vibration and waves material for class VIII SMP. This study used a qualitative approach with a documentation study research method. The number of samples studied was 15 physics learning videos on the Youtube platform with the subject matter of vibrations and waves for class VIII SMP with a video duration of 10 - 20 minutes. The instrument used in this research is a learning video feasibility validation sheet which includes 3 assessment aspects, namely: material aspects, language aspects, and media aspects. The results of this study indicate that physics learning videos on the Youtube platform are classified as very suitable for use but still pay attention to a number of notes for improvement.Keywords: feasibility, youtube platform, physics learning videos.